Stopa zwrotu funduszy emerytalnych i inwestycyjnych jako czynnik determinujący decyzje lokacyjne inwestorów - Trippner, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article underlines the importance of investment for future pensioners and their future benefits not only through obligatory pillars but also through a voluntary third pillar. The level of client interest in funds and investment results have been analyzed. The level of future pension benefits is subject to client investment decision. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 449-456